Public playground inclusive children with disabilities / Seyed Hassan Khalifeh Soltani - Khalifeh Soltani, Seyed Hassan (2013)
The socially marginalize disabled children need proper public playing parks. The present infrastructure and designs do not support this importance and thus needs special attention. This research addresses the participation of institutes, parents, and government to provide better facilities to this section of society which deserves most support and care. Children with disabilities often faced problems at public playgrounds, entertainment and amusement areas, due to the lack of ample provisions to cater for their special needs. The purpose of the study was to investigate the current status of infrastructure and to propose proper design of public playgrounds in Malaysia. Overall ten institutes, universities, hospitals and public playground were visited to examine the availabilities, advantages and disadvantages of public playgrounds for disabled children. Statistical Package for the Social Science software program was used for the data analysis. The findings revealed that there is necessary need to improve and construct well equipped public playgrounds for children with disabilities. The results of this research showed that facilities in the public playgrounds are not enough to accommodate children with special needs. The facilities of the modern day public parks are not standardized. It emphasizes to increase government and NGO funding to create well equipped public parks which accommodate the needs of children with disability. It also stated that government decisions regarding disabled children should be based on knowledge about their special needs in public playgrounds. In this research it has been shown that the current design of playground do not attract the children with disabilities and the concept of modem day public playground does not satisfy their needs. It has also recommended that the design of the public playgrounds should not be discriminatory, and the playgrounds should accommodate the physical needs of disabled children. Based on this research the researcher recommends that proper building regulations are unavoidable. Community awareness is necessary to help disabled children. Designers and builders should adhere to the needs of the disabled children when providing facilities for public play areas.